2023
DOI: 10.1080/10875549.2023.2173708
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Governance on Poverty and Unemployment Control Before and After the Covid Outbreak in the United States

Abstract: Covid-19 presents many social and economic challenges and exacerbates existing ones. One of these challenges is global poverty. Prior to the epidemic, poverty affected the rural population traditionally. Global poverty can spread to urban areas now with COVID-19 outbreak. Poverty increased in the United States in 2020 as the coronavirus outbreak, affecting the economy and rising unemployment. New gures con rm that the recession may have widened the gap between rich and poor, with those at the bottom of the eco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Still, the short‐term situation for workers left vulnerable by the pandemic was dire. Even with the spate of government programmes devoted to remedying the pandemic’s economic effects, poverty rose (Ronaghi and Scorsone, 2023). However, as the pandemic’s negative economic consequences came into fuller view, cities found that the pandemic relaxed some of the common constraints on the policy making process.…”
Section: Emergency Basic Income In Ten Days: the Covid‐19 Crisis Legi...mentioning
confidence: 99%
“…Still, the short‐term situation for workers left vulnerable by the pandemic was dire. Even with the spate of government programmes devoted to remedying the pandemic’s economic effects, poverty rose (Ronaghi and Scorsone, 2023). However, as the pandemic’s negative economic consequences came into fuller view, cities found that the pandemic relaxed some of the common constraints on the policy making process.…”
Section: Emergency Basic Income In Ten Days: the Covid‐19 Crisis Legi...mentioning
confidence: 99%
“…Another study in the corona period (Monserrate et al 2020) [ 14 , 29 ] focused on China, the United States, Italy, and Spain dealing with the indirect positive and negative effects of the COVID-19 epidemic on the environment. While significant correlations were found between air quality improvement and quarantine measures, they also noted the indirect negative effects of reduced waste recycling.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bankruptcy and liquidation rates for corporations during and after the pandemic are unknown, even though companies are fighting for their existence. COVID-19 had affected al the strata of individuals in the United States, however, the low-income were most vulnerable due to certain societal attributes that constrained their opportunities and suffered disproportionately (Ronaghi & Scorsone, 2023). However, it has long been known that contemporary companies play crucial strategic roles in the socioeconomic growth of society due to the sheer magnitude of their financial resources.…”
Section: Introductionmentioning
confidence: 99%